The Effect of Training and Work Motivation on Employee Performance at Bank Indonesia Representative Office of South Sumatra Province - Reza Reza; Marlina Widiyanti; Kemas Muhammad Husni Thamrin; Agustina Hanafi (Journal of Social Science)
This research was conducted with the aim of determining the effect of training and work motivation on employee performance at the Bank Indonesia Representative Office, South Sumatra Province. The population and sample in this research are 50 Non-Officer employees and Assistant Directors of the Bank Indonesia Representative Office for South Sumatra Province in 2023. The results of multiple linear regression analysis show that training and work motivation have a positive and significant effect on employee performance. Training, it is hoped that it is necessary to select the type of training given to employees according to the employee's needs. Choosing a training provider is also important, where the chosen organizer must also be suitable and knowledgeable in this field and have experience and a good image. Work motivation, the role of superiors which is very necessary in looking at relationships between fellow employees. Where if within a division there are colleagues who do not have a harmonious relationship, then the role of superiors is to create a more neutral and professional atmosphere in carrying out work.